Comprehensive technical and economic analysis of the influence of the design of top blowing devices on the main indicators of steel production in oxygen converters (Modern Problems of Metallurgy, 2019)
The article presents the results of the analytical estimation of the impact of the design of the top blowing devices on the main technical and economic indicators of the steelmaking process in oxygen converters with bottom blowing with neutral gas. A comprehensive economic assessment was based on summing up the deviation of relative production costs for crude steel melting (the cost of basic charge materials), without taking into account the cost of upgrading the main process equipment. According to the results of the carried out research, it has been determined that application of the classical design of the oxygen lance, the net calorific value of the converter gas is 10 MJ/m3. In comparison with the classical design, the two-tier, two-circuit and three-tier lances ensure a reduction in the net calorific value of the converter gas by 8.5, 4.4 and 27.1% rel. respectively. When compensating for reducing the net calorific value of exhaust gases with natural gas and taking into account all the main parameters of the steelmaking process, the savings amount to $ 3.23 / ton of steel for two-circuit, $ 6.81 / ton of steel for two-circuit and 11.61 $ / ton steel – for the three-tier lances, compared with the use of the classical design.
Keywords: economic assessment; design of the top blowing lance; technical and economic indicators; oxygen converter; secondary energy resource